Optimasi Konsentrasi Pelarut Etanol Terhadap Aktivitas Analgesik Topikal Daun Mint (Mentha piperita) pada Mencit Putih (Mus musculus) - Sirilus Deodatus Sawu; Devanus Lahardo; Wibowo Wibowo (Fakultas Farmasi Universitas Setia Budi, 2026)
Pain is a natural physiological response of the body due to tissue damage or harmful stimuli where pharmacological treatment generally uses analgesics. Topical analgesics are considered safer because they can minimize systemic side effects. The use of ethanol extract of mint leaves (Mentha piperita) is known to have properties as a topical analgesic so it is necessary to optimize the concentration of ethanol used. The purpose of this study was to test the activity of topical anagesic extract of mint leaves with varying concentrations of ethanol solvents of 50%, 70% and 96% in white mice (Mus musculus). The method used was pain induction using a hot plate. White mice will be divided into 5 groups where each group will receive a different treatment. The soles of the feet of white mice will be smeared with mint leaf extract gel extracted with ethanol solvent concentrations of 50%, 70% and 96% as a test group as well as those who only received gel base and voltaren gel. The results showed that starting from the 30th minute there was a significant difference in the average latency time in all groups (p-value = 0.000). These results indicate that analgesic activity began to appear in the test and positive control groups at 30 minutes compared to the negative control group. The gel containing 96% ethanol extract of mint leaves produced the most optimal topical analgesic activity.